Kekuasaan dan Politik Lembaga Pendidikan Islam - Rofik Aksan (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2022)
The world of politics and power has become inseparable in policy making in all fields, this also happens in the world of Islamic education. Islamic Educational Institutions that are so widely spread throughout the country are of course a strategic issue in power and politics. The purpose of this article is to find out the extent to which Islamic education influences and influences power and politics in Indonesia. This article discusses several things about the political world in Islamic Education Institutions and discusses the relationship between power politics and Islamic education in Indonesia, the political urgency of Islamic education and the position of Islamic education in Indonesia. In addition, several issues will also be discussed including the Strength of Education, Politics and Power in Education, Islamic Education in Indonesia, Education Patterns in Indonesia, as well as four issues that are closely related to the implementation of power-based education, namely, domestication and ignorance, indoctrination, democracy education, and social integration.